Hierarchical grain size and nanotwin gradient microstructure for improved mechanical properties of a non-equiatomic CoCrFeMnNi high-entropy alloy. (30th November 2021) - An, Zibing; Mao, Shengcheng; Liu, Yinong; Zhou, Hao; Zhai, Yadi; Tian, Zhiyong; Liu, Cuixiu; Zhang, Ze; Han, Xiaodong
Highlights: Hierarchical grain size and nanotwin gradient microstructure was created in a novel non-equiatomic CoCrFeMnNi high entropy alloy. A unique condition of complex and multiple strengthening mechanisms is created in this alloy, including grain boundary strengthening, dislocation strengthening, twin strengthening, and hetero-deformation strengthening. The multiple deformation mechanisms mentioned above provide a synergy to enhancing the strength of the alloy without much compromise to the ductility. The designed alloy achieved a yield strength of 750 MPa, an ultimate tensile strength of 1050 MPa and a tensile uniform elongation of 27.5%. Abstract: This study explored a multi-mechanism approach to improving the mechanical properties of a CoCrFeMnNi high-entropy alloy through non-equiatomic alloy design and processing. The alloy design ensures a single-phase face-centered cubic structure while lowering the stacking fault energy to encourage the formation of deformation twins and stacking faults by altering the equiatomic composition of the alloy. The processing strategy applied helped create a hierarchical grain size gradient microstructure with a high nanotwins population. This was achieved by means of rotationally accelerated shot peening (RASP). The non-equiatomic CoCrFeMnNi high-entropy alloy achieved a yield strength of 750 MPa, a tensile strength of 1050 MPa, and tensile uniform elongation of 27.5%. The toughness of the alloy was 2.53 × 10 10 kJ/m 3, which is about 2 times that of the same alloy without the RASP treatment. The strength increase is attributed to the effects of grain boundary strengthening, dislocation strengthening, twin strengthening, and hetero-deformation strengthening associated with the heterogeneous microstructure of the alloy. The concurrent occurrence of the multiple deformation mechanisms, i.e., dislocation deformation, twining deformation and microband deformation, contributes to achieving a suitable strain hardening of the alloy that helps to prevent early necking and to assure steady plastic deformation for high toughness. Graphical abstract: Image, graphical abstract